PENGARUH PENAMBAHAN ABU CANGKANG KERANG HIJAU DAN ZAT ADIKTIF SUPERPLASTICIZER SEBAGAI BAHAN TAMBAH CAMPURAN SEMEN TERHADAP KUAT TEKAN BETON K-400 (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2022)
In thisistudy, the authors took green shell ash and superplasticizer addictive substances as additives in the concrete mixture. This studyiintends to determine the effect of using green shell ash and superplasticizer addictive substances on the compressive strength of concrete K-400. Green shell ash and superplasticizer addictive substances are additives used in concrete mix materials. The total number of test objects in this study were 36 samples, each 9 samples of specimens in 4 variations, namely normal concrete, normal concrete + green shell ash 3% and the addictive substance superplasticizer 1%,inormal concretei+ shell ash green 3% and superplasticizer 2% addictive substance, and normal concrete + green shell ashes 3% and superplasticizer 3% addictive substance. After the addition of green clamshell ash and superplasticizer addictive substance, a compressive strength test of the concrete was carried out, with the obtained characteristic concrete quality on the addition of 3% green clamshell ash and 1% superplasticizer addictive substance, the concrete compressiveistrength value was 403.72 kg/cm2 at the age of 28 days. On the addition of green clamshell ash 3% and 2% superplasticizer addictive substance, the concrete compressive strength value was 411.78 kg/cm2 at the age of 28 day. On the addition of green shell ash 3% and superplasticizer 3% addictive substance, the concrete compressive strength value was 425.48 kg/cm2 at the age of 28 day.